The development nexus and theatre of the youths, by the youths and for the youths in Zimbabwe. - Viriri, Advice; Rwafa, Urther (2016)
The paper investigates the relationship between theatre of the youths by the youths and for the youths and development. In Zimbabwe and as in elsewhere, theatre has historically played a significant role in constructing national identity. Theatre examines the nature of social and cultural change, its importance and structure. The paper depicts the youth's culture embedded in Raisedon Baya's Tomorrow's People (2009), not only as initiators of development but also as the fountain of progress and creativity. The paper pays special attention to the symbolic construction of temporality - the future - within the socio-political and economic context of social change in Zimbabwe. Culture, where theatre is involved, has become an increasingly important factor to the revival of the nations' cultural identities by linking questions of economic and political developments. This phenomenon evolves from the global dynamics of development and change necessitated by internal restructuring of societies. Theatre has turned out to be a potent weapon in privileging youths' action, agency and transformation through recreation and re-enactment of African life. This is possible through intensified intercultural communication supported by the ever-increasing technological advancements. Youths' participation in theatre is not only an essential component of human growth but helps the young to develop their full potential. Theatre becomes a vehicle for youth development by promoting sustainable conflict prevention techniques that provide the much needed space to enhance their competencies and develop skills and attitudes in engaging their peers. The paper further interrogates strategies for ensuring that youths are mainstreamed into society to participate in all social processes.